Growth and survival dynamics of partially cut northern hardwood stands as affected by precut competition and spatial distribution of residual trees. (11th October 2019) - Moreau, Guillaume; Achim, Alexis; Pothier, David
Abstract: Modelling growth and survival dynamics after partial harvesting must take account of the heterogeneous spatial pattern of residual trees that results from the presence of machinery trails. We used data from 23 permanent sample plots in northern hardwood stands to reconstruct the growing environment of individual trees before and after partial harvesting. We modelled harvest probability, growth response and survival probability using a complementary set of explanatory variables that was assembled to reflect the spatial distribution of trees and skid trails prior to and after harvest. Results showed that the distribution of harvested trees was concentrated in skid trails and in their close vicinity. However, this spatial pattern had no significant effect on either the post-cut basal area increment (BAI) or the survival of residual trees. BAI and survival of individual trees were both mostly related to the competitive environment prior to harvest, while post-cut changes in competitive environment had only a marginal effect on growth and survival dynamics. We conclude that selection cuts did not substantially increase the growth and survival of residual trees, likely because tree removal was mostly concentrated near skid trails, where the negative effects of machinery access were highest.